IL-33 and soluble ST2 in follicular fluid are associated with premature ovarian insufficiency - Tang, Maoxing; Sun, Xuedong; Li, Ping; Deng, Weifen; Zhan, Xi; Sun, Peng; Shi, Yuhua (Frontiers in Endocrinology, 2024)
Background: Premature ovarian insufficiency (POI) is a common reproductive disease that is associated with chronic inflammation in ovaries. Interleukin 33 (IL-33) is a proinflammatory IL-1 family cytokine, and functions as an alarmin reflecting inflammatory reaction. Our study aimed to investigate levels of IL-33 and its soluble receptor (sST2) in both follicular fluid (FF) and paired serum during different stages of POI, and evaluate their predictive potentials for POI. Furthermore, we attempted to determine whether IL-33 and sST2 were associated with embryo quality.Methods: A total of 148 women, including 50 patients with biochemical POI (bPOI) (10 IU/L < follicle-stimulating hormone (FSH) ≤ 25 IU/L), 46 patients with POI (25 IU/L＜FSH ≤ 40 IU/L) and 52 age-matched control women with normal ovarian reserve were involved in this study. FF and paired serum were collected from these women. IL-33 and sST2 were measured using quantitative sandwich enzyme-linked immunosorbent assay.Results: FF IL-33 levels were significantly increased in bPOI and POI patients compared to controls. They exhibited positive associations with FSH and luteinizing hormone (LH), whereas negative correlations with anti-Müllerian hormone (AMH), estradiol (E2), testosterone (T) and antral follicle count (AFC). Receiver operating characteristic (ROC) curve analysis showed that for POI prediction, FF IL-33 had a better predictive accuracy (AUC 0.901) with high sensitivity (82.61%) and good specificity (84.62%) than those for bPOI prediction. IL-33 levels in paired serum did not differ among three groups. Regarding sST2, its levels in FF declined with POI progression. Contrarily, they showed negative associations with FSH and LH, but positive correlations with AMH, E2, T and AFC. ROC analysis revealed that FF sST2 had comparatively weak potentials for both bPOI and POI prediction compared to those of FF IL-33. Similarly, there was no significant alteration of sST2 in paired serum among three groups. Additionally, Spearman's correlation analysis revealed that FF IL-33 levels were negatively associated with the rates of Day-3 good-quality embryos (r=-0.206, P=0.012), whereas FF sST2 did not.Our study revealed an increased abundance of FF IL-33, whereas an sST2 deficiency with POI development. This implies that IL-33 and sST2 levels might be associated with the development of POI.